Quick Insight into the Indian Railways Passengers’ Perception on the SERVICE QUALITY – with respect to the Delhi Division - Choudhary, Atul; Bansal, Sanjeev; Sharma, Prashant; Prashaant, Anu (International Journal of Engineering and Technology, 2018)
India with the World’s second largest population that certainly contributes of an increase of passengers’ travelling demands. IR gives the option of cheap as well as comfortable trains for our transportation. However, with growing awareness, passengers look for a better quality of services. This paper refers to the important dimensions which can make a difference in the passengers’ service quality in the Delhi Division of Northern Railways.